TP1-9 Vestibular dysfunction in acute traumatic brain injury. Issue 3 (14th February 2019) - Tsang, K; Marcus, HJ; Paine, H; Sargeant, M; Jones, B; Smith, R; Wilson, MH; Seemungal, BM
Abstract : Objectives: Vestibular dysfunction following traumatic brain injury (TBI) is a major cause of morbidity and unemployment and has impact on the patient's ability to rehabilitate. Chronically, up to a quarter of TBI cases have cryptogenic dizziness and imbalance, possibly due to chronic brain adaptation that masks the diagnosis. Establishing the spectrum of vestibular diagnoses in acute TBI – when they may be more obvious – may aid diagnosis in chronic TBI cases. Design: Prospective audit of referrals to specialist neuro-otology team. Subjects: Consecutive Major Trauma Ward TBI in-patients admitted between June 2014 and May 2015. Methods: All cases were screened by the therapists for vestibular symptoms and/or signs and referred for specialist neuro-otology review. Results: Of 111 patients screened, 96 had features of vestibular dysfunction. Of 96 cases, SYMPTOMS (i.e. subjective report) included: – imbalance (58.3%) – headache (50%) -dizziness (40%) Of 96 cases, SIGNS (i.e. examination) included: – gait ataxia (75.5%) – broken smooth pursuit (61.2%) – positive Hallpike (51%) – positive head impulse test (18%). The data indicate that BPPV affects 49% and headache with migraine-like features affect 40.8%. Acute peripheral unilateral vestibular loss affects 18% TBI cases. Conclusions: Vestibular dysfunction in TBI is common, typically involving peripheral and central structures, often in the same case, and requires specialist neuro-otological management.